Valores interpersonales asociados con la conducta infiel de estudiantes de educación superior en Cartagena de Indias - Geney, Elías Rafael (2024)
The present investigation was analyzed the existent relation between interpersonal values and infidelity in students with superior education in the city of Cartagena de Indias (Colombia). A descriptive, correlational and cross-sectional study between interpersonal values and unfaithful behavior was executed in 928 subjects, doing also two linear regression analysis between sexual infidelity, desire to sexual infidelity and other social and demographical variables. The results indicate that individualistic values such as recognition and leadership can promote infidelity, while those orient towards the common good can prevent it; sex being the most relevant social and demographical variable to explaining this behavior and the thoughts related to infidelity.